Le contrôle judiciaire européen de la prison: les droits de l'homme au fondement d'un panoptisme inversé? - Cliquennois, Gaëtan (Déviance et société, 2014)
Belgium is characterised by the weakness of its own national judicial control over its prisons, both by the judiciary and administratively. This poor control can be explained by the refusal by the Council of State to exert control over the prison administration and the division of competences between the judicial and administrative orders. This weakness is also considerably reinforced by Belgium’s failure to ratify the Optional Protocol of the UN which implies a lack of independence for the surveillance commissions and for the Central Committee for surveillance that are the main Belgian bodies responsible for internal control over prisons. Therefore, control over Belgian prisons is more and more exercised by the Council of Europe and in particular the European Court of Human Rights, the Committee of Ministers and the Committee for the Prevention of Torture, which have extended the scope of their supervision to cover suicides, illegal detention, healthcare and insanity.